Cropping system intensification and nutrient dynamics in the Great Plains: implications of cover crop and nitrogen fertilizer management - Correira, Alexis (My University, 2026)
Understanding how land management decisions impact the agronomic outputs, ecology, and soils in agroecosystems can empower farmers to make the best choices for their own operations. No-till has revolutionized agriculture in Kansas, with approximately 12 million acres under no-till recorded in 2022. However, cover crops have not gained the same traction in the state. This is likely due to the perceived financial and systemic risks associated with cover crops. Despite gaining national interest, there is still limited understanding of how cropping systems respond to the inclusion of cover crops at more local levels. The goals of the cover crop studies were to better understand nutrient dynamics and ecologic response to cover crop management in northeast Kansas. The final chapter is an exploratory study on the effects of long-term fertility management, looking at the Magruder Plots in Stillwater, Oklahoma. The first experiment explores the relationship between cover crop selection and nitrogen dynamics in a wheat-corn-soybean rotation. The study took place from 2020-2025 within a long-term cover crop experiment at Ashland Bottoms. The treatments included a chemical fallow check (CF), cover crops (legume, grass, legume/grass mix, a diverse mix), and double-crop soybeans (DSB, [Glycine max (L.) Merr.]) planted after wheat (Triticum aestivum L.) and before corn (Zea mays) in a no-till wheat-corn-soybean rotation. Five nitrogen fertilizer rates (0, 45 ,90, 180, and 270 kg ha⁻¹) were applied to the corn within each treatment. Corn development was monitored throughout the growing season, and soil nitrogen was analyzed before planting cover crops, after terminating cover crops, and after corn harvest to determine total nitrogen balance in the system. There was a significant interaction effect (P < 0.001) of fallow replacement and nitrogen rate for most response variables. System yields were generally highest after the CF and DSB treatments, driven by corn yields. Additional nitrogen may overcome corn yield drag following some cover crops, but moisture use after cool-season cover crops is still a concern. The next experiment explored the potential ecosystem services of a late-terminated cereal rye cover crop before corn. Although cover crops in Kansas are typically terminated 2-4 weeks prior to cash crop planting, there may be situations where late-burndown or planting into a living cover crop may be necessary, and some advocates of regenerative agriculture promote planting green as the most desirable practice. Three different termination dates were tested – 4 weeks prior to planting (early), 3 days prior to planting (late), and at planting (green), as well as a check treatment with no cover crop planted. Insect assessments did not indicate a significant effect of termination timing on beneficial insects. There were significant yield losses observed in cover crop treatments some years, especially where corn was planted green. Cover crop biomass in 2022 was 64% lower than what was observed in 2021, and cover crop biomass in 2023 was 84% lower than in 2021. The control and early termination treatments resulted in significantly higher yields than the late and green treatments in 2022, but only the green treatment resulted in significantly reduced grain yields in 2021. The late termination and planting green treatments resulted in a 1.38 and 3.75 Mg ha yield penalty in 2021 and 2022, respectively. In 2023, corn grain yields were not statistically different between treatments, and the average yield in 2023 was 32% lower than the highest yields in 2021. Cereal rye biomass was lowest in 2023, perhaps due to limited precipitation during the cover crop growing season. Corn root biomass was significantly affected by cereal rye termination timing, with the lowest values in planting green plots. This could be linked to increased instances of Pythium leading to radical root rot. Yield losses after planting green may be attributed to increased seedling disease, immobilization of soil nitrogen, and stored soil water uptake by the living cereal rye cover crop. The final experiment is an exploratory study on the long-term effects of soil fertility management on inherent soil properties. Soil mineralogy is historically thought to be an inherited soil quality originally derived from parent materials. However, recent studies suggest that soil acidification from agricultural land use may be altering soil minerals in shorter time scales, challenging the view that mineralogical changes only occur at the deep time scale. The objectives of this research were to stress the importance of basic soil mineralogy knowledge for agronomists and to address whether long-term soil fertility management increases the proportion of highly-weathered clay minerals. Soil samples were pulled from the historic Magruder plots in Stillwater, Oklahoma at Oklahoma State University. The plots were moved in 1947 and consistently managed since then. There are six fertility treatments applied to continuous wheat plots. Soil cores were pulled from each plot down to one meter. Samples were prepared for clay mineralogical assessments and x-rayed using the Jackson (1975) method. In the surface samples, organic carbon was highest in the manure plot, base saturation was highest in the manure plot and NPK with lime amendment plot, and pH was lowest in NP and NPK plots. Mineralogical differences were not observed in the XRD patterns or in thin soil thin section, but chemical analyses indicate increased weathering in NP and NPK plots.
Keywords: Cover crops; Nitrogen; Mineralogy; Corn; Cereal rye